Penerapan pijat kaki Terhadap Peningkatan Kekuatan Otot Pada Pasien Stroke - Rauf, Rahmattullah; Suharto, Dewi Nurviana (Madago Nursing Journal, 2023)
Background Stroke is a central nervous system function disorder in the form of blockage of brain blood vessels or rupture of blood vessels in the brain, symptoms that appear in hemiparesis disease, namely a decrease in muscle strength, one of the independent nursing interventions in dealing with decreased muscle strength by giving foot massage. Research Methods: This study uses a descriptive method with a case study approach. Sample: 1 stroke patient who experienced a decrease in muscle strength. Results: the study found that stroke patients experienced complaints of weakness on the right side of the body, muscle strength on the right 1. Nursing diagnoses were: physical mobility barriers, ineffective cerebral tissue perfusion, and damage to skin integrity. Mobilization support nursing interventions, Improved cerebral perfusion, skin integrity care. Nursing implementation was carried out for 6 days. Evaluation after applying foot massage nursing problems that arise in patients can be resolved. Conclusion: the application of foot massage can increase muscle strength there is a change in the value of muscle strength in stroke patients from a value of 1 to a value of 4 on day 6. Suggestion: it is hoped that it can provide independent nursing interventions as a companion to pharmacological therapy to overcome nursing problems that exist in non hemorrhagic stroke patients.